Sutardji Calzoum Bachri : sastrawan Indonesia penerima Anugerah Mastera tahun 2006. - Pusat Bahasa (Indonesia) (Jakarta : Pusat Bahasa, Departemen Pendidikan Nasional, 2006)
Biographical sketches of Sutardji Calzoum Bachri, an Indonesian poet, recipient of the Mastera Award.
Keywords: Bachri, Sutardji Calzoum; Indonesian poet -- Biography